Assisted reproductive technology in Japan: A summary report for 2021 by the Ethics Committee of the Japan Society of Obstetrics and Gynecology - Yukiko Katagiri; Seung Chik Jwa; Akira Kuwahara; Takeshi Iwasa; Masanori On; Keiichi Kato; Hiroshi Kishi; Yoshimitsu Kuwabara; Fuminori Taniguchi; Miyuki Harada; Akira Iwase; Yutaka Osuga (Reproductive Medicine and Biology)
Abstract Purpose The Japan Society of Obstetrics and Gynecology (JSOG) registry gathers comprehensive data from registered assisted reproductive technology (ART) facilities in Japan. Herein, we report 2021 ART cycle characteristics and outcomes. Methods Descriptive statistics were used to summarize and analyze 2021 data. Results In 2021, 625 ART facilities participated in the registry; 27 facilities did not conduct ART cycles and 598 registered treatment cycles. In total, 498 140 cycles were registered, and there were 69 797 neonates (increases of 10.7% and 15.5%, respectively, from the previous year). The number of freeze‐all in vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI) cycles decreased in 2021; the number of neonates born was 2268 for IVF‐embryo transfer (ET) cycles and 2850 for ICSI cycles. Frozen–thawed ET (FET) cycles increased markedly from 2020 (11.2% increase). In 2021, 239 428 FET cycles were conducted, resulting in 87 174 pregnancies and 64 679 neonates. For fresh transfers, the total single ET, singleton pregnancy rate, and singleton live birth rates were 82.7%, 97.0%, and 97.3%; for FET, these rates were 84.9%, 96.9%, and 97.1%. Conclusions The 2021 Japanese ART registry analysis showed marked increases in both total treatment cycles and live births from the previous year.